Improving Students' English Speaking Achievement Through A Group Podcast Strategy - Nasution, Nurfadila; Saragih, Mandra (Journal of English Language and Education, 2026)
This study aims to improve the English speaking skills of 6th grade high school students at Wittaya Islamic School in Thailand through the application of a group podcast strategy. This study used the Classroom Action Research (CAR) method, which was carried out in two cycles. The problems encountered were the students' low English speaking skills due to limitations in constructing spoken sentences, low self-confidence, limited vocabulary, and psychological factors such as shyness and fear of making mistakes. The results showed a significant improvement in three main indicators: teacher activity increased from 68% (poor category) to 85% (excellent category), student activity increased from 60.73% (fair category) to 75% (good category), and student test scores increased dramatically from 52.12% (poor category) to 84.62% (excellent category). The most notable improvement occurred in test scores, with a difference of 32.5%. This study proves that the group podcast strategy is effective in improving students' English speaking skills because this strategy encourages collaboration, boosts confidence, expands vocabulary, and creates a meaningful and contextual learning environment